A genogeographic study of the Kyrgyz mountain merino via microsatellite markers - A. В. Bekturov; Zh. T. Isakova; V. N. Kipen; T. Dzh. Chortonbaev; S. B. Mukeeva; S. K. Osmonaliev; К. A. Aitbaev (Вавиловский журнал генетики и селекции)
The aim was to ascertain the genetic and geographical structure of the Kyrgyz mountain merino (KMM). We analyzed DNA samples of 109 Kyrgyz mountain merino specimens, bred in three state breeding factories (STB), including“Orgochor” in the Issykul Province,“Katta-Taldyk” in the Osh Province and STb named after Luschikhin in the Talas Province. We identified 126 alleles in 12 microsatellite markers (McM042, INRA006, McM527, ETH152, CSRD247, OarFCB20, INRA172, INRA063, MAF065, MAF214, INRA005, INRA023). There were 6 to 16 alleles in each locus (mean 10.500 ± 0.957 alleles per locus). We identified 67 rare alleles (prevalence less than 5.0 %), which made up 53.2 % of all alleles found. The greatest number of rare alleles was found in STR-markers of CSRD247, INRA023, INRA005, INRA006, MAF214 and OarFCB20. For each group, there were individual differences in the distribution of allele frequencies across all the STR loci studied. The most significant of them were as follows: with regard to the McM042 locus, allele 87 was major in the TALAS and OSH groups (35.6 and 45.7 %, respectively), whereas allele 95 was major in the ISSYK-KUL group (36.2 %); allele 154 was major in all groups with regard to the INRA172 locus, but it was 1.25 times less prevalent in the ISSYK-KUL and 1.66 times less prevalent in the OSH groups compared to TALAS (55.2 and 41.4 %, respectively), whereas alleles 156 and 158 were found only in the ISSYK-KUL group. Considering the ETH152 locus, 186 allele prevalence in the TALAS group was 51.1 %, but allele 190 was also markedly prevalent in the ISSYK-KUL and OSH groups, 34.5 and 34.3 %, respectively. The genetic division of the studied groups of KMM (with K from 3 to 10) was homogeneous – the contribution of each subcluster was equivalent. The AMOVA analysis revealed that the groups are located equidistantly. To conclude, the genetic diversity of the Kyrgyz mountain merino in three state breeding factories of the Kyrgyz Republic was high and comparable with each other.